Combination of innovative technologies and historic heritage in spiritual and moral education of cadets - Olga V. Barskaya (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is aimed at formulating recommendations for the use of innovative forms of cadets’spiritual and moral education for the creative connection of historical content and modern technologies in the upbringing process of military educational institutions.For that purpose the objectives, novelty, methodological framework and methods of the research are indicated.The topicality of the issue under concern is proved on the basis of a survey conducted within the naval cadet community, and the analysis of the problem study extent in modern domestic and foreign science is carried out. Based on the modern scientific researches, the definitions to the terms of spirituality, spiritual and moral education and innovative pedagogical technology were given and the functions of using information-communicative technologies in the process of education were figured out. The most essential part of the paper is dedicated to the methodological recommendations towards virtual excursion and competition-project technologies application in the process of spiritual and moral education of naval cadets. The project, which suggests the combination of information technologies use and archive sources and printed materials containing local history facts study by cadets was worked out and the topics for the similar projects realization in the future were offered.